2022
DOI: 10.1038/s41389-022-00423-5
|View full text |Cite
|
Sign up to set email alerts
|

Diltiazem inhibits breast cancer metastasis via mediating growth differentiation factor 15 and epithelial-mesenchymal transition

Abstract: Migration and metastasis commonly happen to triple-negative breast cancer (TNBC) patients with advanced diseases. In many studies, it has been suggested that epithelial-mesenchymal transition (EMT) is one of the key mechanisms triggering cancer metastasis. Accumulating evidence has proven that calcium channel blockers mediate cell motility. Therefore, we attempt to investigate the effects of diltiazem, which has been selected from several FDA-approved clinical calcium channel blockers, on EMT in TNBC. By using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…On the other hand, a high level of GDF9 was associated with good progression in breast tissues (47). Interestingly, a recent study showed that Diltiazem, a calcium channel blocker, was able to prevent EMT and reduce migration and invasion of TNBC cancer cells by up-regulating GDF15, with GDF15 itself having the similar inhibitory effect on invasiveness and EMT (48). This is in line with the inverse correlation, between GDF15 and EMT markers, observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, a high level of GDF9 was associated with good progression in breast tissues (47). Interestingly, a recent study showed that Diltiazem, a calcium channel blocker, was able to prevent EMT and reduce migration and invasion of TNBC cancer cells by up-regulating GDF15, with GDF15 itself having the similar inhibitory effect on invasiveness and EMT (48). This is in line with the inverse correlation, between GDF15 and EMT markers, observed in the present study.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, DTZ exhibited a beneficial role against the ICV-STZ-induced SAD rats in various aspects by attenuating the altered cognitive deficits, anti-oxidative defense parameters, pro-inflammatory cytokines, and APP expression. In experimental animal models, DTZ has been utilized in a variety of doses ranging from 5 mg/kg to 800 mg/kg for up to 10–40 days [ 57 , 58 , 59 ]. In this study, the treatment doses employed (10, 20, and 40 mg/kg) were selected after performing the pilot study and referring to the previous reports [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, DTZ exhibited a beneficial role against the ICV-STZ-induced SAD rats in various aspects by attenuating the altered cognitive deficits, anti-oxidative defense parameters, pro-inflammatory cytokines, and APP expression. In experimental animal models, DTZ has been utilized in a variety of doses ranging from 5 mg/kg to 800 mg/kg for up to 10-40 days [57][58][59]. In this study, the treatment doses employed (10, 20, and 40 mg/kg) were selected after performing the pilot study and referring to the previous reports [29].…”
Section: Discussionmentioning
confidence: 99%